LOW-MODULUS ARCTIC CABLE MATERIALS. - Kell, R. M.; Bennett, Bailey; Stickney, P. B. (1965)
Work was completed on the second quarter of a program to develop more flexible insulation and jacketing for coaxial cables. A promising insulating material was developed by blending polyethylene resins with polyisobutylene or other hydrocarbon elastomers. Physical and electrical properties measured thus far appear to meet initial specifications. Chemical and radiation vulcanized polymers were shown to have several deficiencies which limit their present consideration as insulation. More work would have to be done to adapt these vulcanized polymers to coaxial cable use. To date no fluorocarbons have been uncovered which have the flexibility required by Arctic cable. Commercial polymers consisting primarily of ethylene copolymers and urethane elastomers were evaluated jor jacketing. The best overall results were exhibited by an ethylene copolymer. However, some urethanes appeared promising and will be investigated further. (Author)